20.3k views
4 votes
3x + 5 - (5x + 8) = -4x - 7

User Mobyte
by
4.5k points

2 Answers

6 votes

Answer:

x = -2

Explanation:

Step 1: Simplify both sides of the equation.

3x+5−(5x+8)=−4x−7

3x+5+−1(5x+8)=−4x−7(Distribute the Negative Sign)

3x+5+−1(5x)+(−1)(8)=−4x−7

3x+5+−5x+−8=−4x−7

3x+5+−5x+−8=−4x+−7

(3x+−5x)+(5+−8)=−4x−7(Combine Like Terms)

−2x+−3=−4x−7

−2x−3=−4x−7

Step 2: Add 4x to both sides.

−2x−3+4x=−4x−7+4x

2x−3=−7

Step 3: Add 3 to both sides.

2x−3+3=−7+3

2x=−4

Step 4: Divide both sides by 2.


(2x)/(2) = (-4)/(2)

x = −2

User Svein Terje Gaup
by
4.8k points
2 votes

Answer:

Standard form:

2x + 4 = 0

Factorization:

2(x + 2) = 0

Solutions:

x = −4 /2 = −2

User Mondano
by
5.4k points